Developing class scheduler using genetic algorithm - Marcial, Dave E. (Philippine computing journal)
This paper discusses the applicability of Genetic Algorithms as a solution in developing an automated class scheduler system. Constraints like time conflicts, room conflicts, and professor information were organized, considered and solved in the duty...